Capacitive pressure sensing unit for racket sports - Zheng, Y.-J.; Wang, W.-C.; Chen, R.; Chiu, W.-H.; Chen, Y.-Y.; Lo, C.-Y. (2021 IEEE Sensors 31 Oct.-3 Nov. 2021, 2021)
To sense the finger forces applied on a racket, a capacitive pressure-sensing unit is developed in this work, which is able to quantify the performance of local muscles. In addition, the dynamic window of the sensor is expanded, and the unit is designed in an ergonomic way. Not only the micro electro mechanical system process technology and practical integration are presented for implementation details, but also the force simulation, measurement calibration, and experimental results are provided to prove the feasibility of this work. Although badminton was demonstrated in this work as a proof-of-concept, this work can be beneficial for players of racket sports, in which sophisticated force changes on fingers is importantly linked to the performance.